THE EFFECT OF CORPORATE SOCIAL RESPONBILITY (CSR) AND COMPANY REPUTATION ON COMPANY VALUE WITH PROFITABILITY AS MODERATION (STUDY OF PHARMACEUTICAL COMPANIES LISTED ON THE IDX IN 2019-2022) - Dwi Arsitasari; Hadiah Fitriyah Fitriyah (PT. Antis International Publisher, 2025)
Objective: This research aims to determine the effect of CSR and company reputation on company value with profitability as moderation. Method: This sample uses pharmaceutical companies registered on the IDX in 2019-2022. The data analysis technique used is descriptive statistical analysis, using the MRA (Moderate Regression Analysis) multiple regression analysis method, using the Statistical Package for Social Sciences (SPSS) software version 26. Result: The results of this research prove that CSR has a positive effect on company value. Meanwhile, the company's reputation has a positive effect on company profitability. The existence of profitability as a moderating variable can moderate the company's reputation well; however, CSR weakens it. Novelty: The implication of this research is to increase information for investors about the importance of CSR communication and company reputation to company value.